Cognitive Development in the Digital Age: A Cross-Cultural Perspective - Wijaya Wijaya; Rashid Rahman; Aiman Fariq (Yayasan Adra Karima Hubbi, 2025)
The pervasive integration of digital technologies into adolescents’ lives has fundamentally altered their developmental environments. While the cognitive impact of this “digital age” is widely debated, research often overlooks how these effects are moderated by cultural context, which shapes how technology is adopted and utilized. This study aimed to conduct a cross-cultural comparison of the relationship between specific patterns of digital technology engagement and key cognitive functions, including attention, working memory, and problem-solving skills, among adolescents. A cross-sectional study was conducted with 400 adolescents (aged 14-16) from the United States (n=200) and South Korea (n=200). Participants completed standardized cognitive tests and a Digital Usage Questionnaire. Multiple regression analyses were used to examine the interaction between culture and technology use on cognitive performance. A significant interaction effect emerged. In the U.S. sample, higher social media use correlated with weaker sustained attention. In the South Korean sample, high engagement in collaborative online gaming was positively associated with enhanced problem-solving skills and working memory. The cognitive correlates of technology use differed significantly across cultures. The cognitive impact of the digital age is not universal but is profoundly shaped by cultural values that guide technology engagement.